The interruption of transmission of onchocerciasis in Kaduna, Kebbi and Zamfara states, Nigeria: another milestone achievement. (21st September 2022) - Isiyaku, Sunday; Igbe, Michael; Madaki, Suzie; Hamill, Louise C; Ndongmo, Patrick; Adamani, William; Bush, Simon; Shu'aibu, Joy; Elhassan, Elizabeth; Saka, Yisa; Anyaike, Chukwuma; Akpan, Nse Michael; et al.
Abstract: Background: More than 40 million people live in onchocerciasis-endemic areas in Nigeria. For at least 19 y, mass drug administration (MDA) with ivermectin was implemented with at least 65% total population coverage in Kaduna, Kebbi and Zamfara states. Impact surveys done using skin biopsies yielded no infections. Serological and entomological assessments were undertaken to determine if onchocerciasis transmission had been interrupted and MDA could be stopped. Methods: The presence of onchocerciasis-specific immunoglobulin G4 antibody was measured by enzyme=linked immunosorbent assay conducted on dried blood spots collected from 5- to 9-year-old children resident in each state. O-150 polymerase chain reaction testing of Simulium damnosum s.l. heads for Onchocerca volvulus DNA was done on black flies collected by human landing capture and Esperanza window traps. Results: A total of 9078 children were surveyed across the three states. A total of 6139 vectors were collected from Kaduna state, 129 from Kebbi state and 2 from Zamfara state; all were negative. Kebbi and Zamfara states did thousands of hours of black fly catching and intensive river prospecting. The resulting low fly catch was due to a low fly population incapable of sustaining transmission. Conclusion: Onchocerciasis transmission has been interrupted and the three states meet World Health Organization thresholds: seropositivity in children <0.1% and <1/2000 infective black flies with 95% confidence. The 2.2 million people in Kaduna state and 4 million in Kebbi and Zamfara states no longer need ivermectin for onchocerciasis.